2018
DOI: 10.1161/strokeaha.118.021706
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Nicotine in the Development of Intracranial Aneurysm Rupture

Abstract: Background and Purpose: Tobacco cigarette smoking is considered to be a strong risk factor for intracranial aneurysmal rupture. Nicotine is a major biologically-active constituent of tobacco products. Nicotine’s interactions with vascular cell nicotinic acetylcholine receptors containing α7 subunits (α7*-nAChR) are thought to promote local inflammation and sustained angiogenesis. In this study, using a mouse intracranial aneurysm model, we assessed potential contributions of nicotine exposure and activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“… 33 Nicotine exposure may further promote aneurysmal rupture through actions on vascular smooth muscle cell nicotinic acetylcholine receptors containing α7 subunits. 34 Smoking might also affect CVD risk through antioestrogenic effects, observed in both women and men. 35–37 …”
Section: Discussionmentioning
confidence: 99%
“… 33 Nicotine exposure may further promote aneurysmal rupture through actions on vascular smooth muscle cell nicotinic acetylcholine receptors containing α7 subunits. 34 Smoking might also affect CVD risk through antioestrogenic effects, observed in both women and men. 35–37 …”
Section: Discussionmentioning
confidence: 99%
“…Differences in aneurysm morphology and size have been proposed between smoking and non-smoking patients 8 , 9 . It is thought that nicotine promotes local inflammation and sustained angiogenesis, resulting in downstream changes and alteration of aneurysm morphology 10 . Here, we present a large cohort of 505 patients with anterior communicating artery (ACoA) aneurysms to assess morphological features associated with ruptured aneurysms, as well as, the association of patient characteristics, including age and tobacco use, with those morphological features.…”
Section: Introductionmentioning
confidence: 99%
“…[57][58][59] Indeed two genes in our model, LRRN3 and GPR15, are among the top differentially expressed genes in blood between current and never smokers according to a meta-analysis by Huan et al 60 Their presence in our predictive model may be because of the higher proportion of smokers in IA group or because these genes are capturing biological mechanisms related to smoking that are important in IA pathogenesis, such as endothelial dysfunction. [61][62][63] Still, when we performed covariate analysis using MatchIt to create subgroups with similar distributions of covariates between IA and control groups, we found that no one subgroup had signi cantly higher misclassi cation rates. For instance, 61% of all subjects in "Subclass 5" were smokers, and this subgroup had a misclassi cation rate of 13%.…”
Section: Discussionmentioning
confidence: 91%